Co3ZnC/Co nano heterojunctions encapsulated in N-doped graphene layers derived from PBAs as highly efficient bi-functional OER and ORR electrocatalysts. Issue 23 (27th May 2016) - Su, Jianwei; Xia, Guoliang; Li, Ran; Yang, Yang; Chen, Jitang; Shi, Ruohong; Jiang, Peng; Chen, Qianwang
Abstract : Unique nano heterojunction structures encapsulated in highly nitrogen doped graphene layers were synthesized in situ by one-step annealing of PBAs serve as bi-functional ORR and OER catalysts. Abstract : The oxygen evolution reaction (OER) is a key half reaction involved in electrochemical water splitting. However, it is kinetically not favored and hence requires highly active electrocatalysts. Non-precious metal based catalysts have emerged as the most promising materials for the replacement of state-of-the-art noble metal catalysts. However, more progress is still needed to improve the activity and stability of these catalysts. Herein, we synthesized Co3 ZnC/Co nanojunctions encapsulated in highly nitrogen doped graphene layers by one-step annealing of Prussian blue analogues (PBA). The catalyst shows a low overpotential of only 366 mV at 10 mA cm −2, which is superior to state-of-the-art commercial RuO2 catalysts. Besides, it exhibits a better performance compared with similar metallic carbide-based catalysts towards ORR with an onset potential and cathodic peak potential at 0.912 V and 0.814 V, respectively.